2002
DOI: 10.1080/0042098022000033926
|View full text |Cite
|
Sign up to set email alerts
|

Rural Industrialisation and Internal Migration in China

Abstract: To avoid the problems of overcrowding and urban unemployment that are associated with overurbanisation observed in other developing countries, China has, since the late 1970s, actively pursued a strategy of rural industrialisation by encouraging the development of rural industries which provide employment opportunities for the surplus labour in agriculture. In this paper, we examine the impact of rural industrialisation on migration using data from the 1990 China Population Census. We use robust estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…Fueled by economic reform and the improved efficiency of agricultural production, the rural labor force finds itself no longer needed for agricultural work, and so must seek work elsewhere (Hare & Zhao, 2000;Zhao, 2003). Since the late 1980s, it has become increasingly difficult to reinforce this policy because employers enjoy greater flexibility in hiring people (Liang, Chen, & Gu, 2002;Zhang, 2004). Internal migration has fueled an increasing movement of workers toward the industrial regions.…”
Section: "They [Members Of the Guanxi Network] Will Usually Recommendmentioning
confidence: 99%
“…Fueled by economic reform and the improved efficiency of agricultural production, the rural labor force finds itself no longer needed for agricultural work, and so must seek work elsewhere (Hare & Zhao, 2000;Zhao, 2003). Since the late 1980s, it has become increasingly difficult to reinforce this policy because employers enjoy greater flexibility in hiring people (Liang, Chen, & Gu, 2002;Zhang, 2004). Internal migration has fueled an increasing movement of workers toward the industrial regions.…”
Section: "They [Members Of the Guanxi Network] Will Usually Recommendmentioning
confidence: 99%
“…The traditional centrally planned economy has been transformed into a market based economy, with accompanying processes of industrialization and urbanization. These processes have impacted on the social, economic and environmental landscape of both urban and rural China, with key trends including mass migration from rural to urban areas and the development of 'villages-in-the-city' (chengzhongcun) of rural migrant workers (Chan, 2010;Chung, 2010;Liang et al, 2002;Song et al, 2008); the growth of urban sprawl and the loss of agricultural land in peri-urban districts (Lin, 2006;Liu et al, 2010b;Wang and Scott, 2008;Wei and Zhao, 2009;Yu and Ng, 2007); and rural industrialization, especially in districts close to cities with highly liberalized economies (Peng, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the reform period since 1978, these strategies have particularly emphasized the implementation of 'household responsibility system', the establishment of township and village enterprises (TVEs) (Liang et al, 2002;Putterman, 1997;Shen and Ma, 2005;Xu and Tan, 2002), and social and infrastructural developments such as road construction, irrigation, electrification and investments in health and education provision -adopted in 2006 under the slogan of 'Building a New Countryside' . However, research has revealed spatial variations in the implementation of these policies, demonstrated the importance of local actors in mediating change, and questioned the appropriateness of strategies in some districts (Hang and Iseman, 2009;Long et al, 2009bLong et al, ,c, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the increasing rural housing land, the rural population decreased with the key trends including mass migration from rural to urban areas and the development of 'villages-in -city'(chengzhongcun) of rural migrant workers (Chan, 2010;Liang, Chen, & Gu, 2002;Chen et al, 2014;Song et al, 2008;. with an annual growth rate of 1.6%, which was far greater than 0.1% that of rural housing land (MLRC, 2009;NBSC, 2009).…”
Section: Introductionmentioning
confidence: 99%